Day of the Dead Exhibit
Day of the Dead Film Summary Film Duration - 43:19 Denise Lugo behind camera Video starts at The Latino Museum with children in the back offices of the museum. Cynthia and Husband are shown, Last name unknown. 1:36 - Next is a view of tables and other installations for the Day of the Dead celebration Close ups on a lot of the items on the tables: Flowers, candles, pictures, candies, table cloths, blankets, clothing, pottery, fruit and offering bowls. 10:25 - Short clip of Hispanic workers outside in the parking with dirt used for an installation. 11:06 - Dresses, as part of installation, are shown close-up. 15:05 - 3 Artists shown setting up dirt plot for part of installation. Sand sculpture of skeleton and flowers. 18:02 - In another room of TLM, an artist preps his plot of sand to be used as a sculpture. The artist discusses his sculpture idea with teenagers who will help construct the sculpture. Back and forth between both sand sculptures and the process of them building. 22:56 - 3 Artists with skeleton begin process of sprinkling color onto their sculpture. Families are on hand to watch process; Adults and children 30:34 - A Marching band is brought in and plays some songs. 34:23 - Exterior shot of building with the sound of the band in the background. Back to the interior and shots of the crowd inside looking at the installations. 42:40 - Last shots shows the completion of both Sand sculptures. The artist and children/teenagers involved in the creation of the second sand sculpture, including the artist's original drawing, is shown.